2016
DOI: 10.1111/eve.12676
|View full text |Cite
|
Sign up to set email alerts
|

The anthelmintic effects of five plant extracts on the viability of Parascaris equorum larvae

Abstract: Summary Ascariasis is a very common parasitic disease in equids, especially in young horses. Despite the use of anthelmintic drugs, resistance has been frequently reported in populations of Parascaris equorum. As a result, herbal preparations are proposed for current control strategies. In this study, a modified method was used for hatching the eggs of P. equorum. After hatching, the effects of methanolic extract of Artemisia dracunculus, Eucalyptus camadulensis, Mentha pulegium, Zataria multiflora and Allium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Microencapsulated, plant-based mixed functional food composed of several compounds isolated from EOs, given perorally to the pigs daily in a dose of 1.0 mg/kg after fourteen days significantly reduced worm counts (76.8%), female worm counts (75.5%), FEC (68.6%), and worm volume (62.9%) (Kaplan et al 2014). In a study of Rakhshandehroo et al (2017), methanolic extracts of Artemisia dracunculus and Mentha pulegium at all tested concentrations (50, 75, 100 and 125 mg/mL) had significant lethal effects on larvae of Parascaris (P.) equorum, which is common causative agent of disease in equids, especially young horses. Botanical anthelmintics have also shown an effect against various nematodes in dogs and cats.…”
Section: Studies That Examined the Antiparasitic Efficacy Of Plant Pr...mentioning
confidence: 95%
“…Microencapsulated, plant-based mixed functional food composed of several compounds isolated from EOs, given perorally to the pigs daily in a dose of 1.0 mg/kg after fourteen days significantly reduced worm counts (76.8%), female worm counts (75.5%), FEC (68.6%), and worm volume (62.9%) (Kaplan et al 2014). In a study of Rakhshandehroo et al (2017), methanolic extracts of Artemisia dracunculus and Mentha pulegium at all tested concentrations (50, 75, 100 and 125 mg/mL) had significant lethal effects on larvae of Parascaris (P.) equorum, which is common causative agent of disease in equids, especially young horses. Botanical anthelmintics have also shown an effect against various nematodes in dogs and cats.…”
Section: Studies That Examined the Antiparasitic Efficacy Of Plant Pr...mentioning
confidence: 95%
“…However, it has been shown that allicin, a molecule that belongs to the organosulfur group, is the most abundant (10 mg g −1 matter fresh) in Allium sativum, and that it is responsible for its characteristic odor when crushed, as well as the inhibition it exerts on the growth of Babesia caballi and Theleria equi at concentrations of 10 and 100 µM, respectively [100,101]. Contrary to this, Buono et al [14] reported that in the short term (15 days), there is no effect of Allium sativum on the elimination of intestinal strongyle eggs in horses, while when evaluating the control of Parascaris equorum using five plants with anthelmintic properties, only Artemisia dracunculus, Mentha pulegium, and Zataria multiflora showed potential for larval control from the first instar to the fourth at concentrations greater than 100 µg mL −1 , and Eucalyptus camadulensis and Allium sativum did not exert effective control over this parasite [102].…”
Section: Plant Bioactive Compounds For the Control Of Gatrointestinal...mentioning
confidence: 97%
“…infection. For example, extract of Artemisia dracunculus, Mentha pulegium, Zataria multiflora have potential to be used as anthelmintic for the control of ascariasis in horses [30]. This requires further research on their activity.…”
Section: Table 2 Estimated Mean Faecal Egg Count Reduction Following mentioning
confidence: 99%